Implementasi REST API Web Services pada Aplikasi Sumber Daya Manusia - Roselilie Simbulan; Joko Aryanto (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
Human resources management is a vital component within any organization, serving as a valuable asset and a driving force. However, many companies face challenges when it comes to managing employee data, processing leave requests, and generating accurate salary reports, often relying on cumbersome manual processes. This research aims to address these challenges by implementing a REST API (Representational State Transfer Application Programming Interface) in a web-based human resources application. The REST API is carefully built using the Laravel framework, adhering to REST architecture principles to ensure security during internet-based information exchange. The development methodology employed for this application is the waterfall method, a sequential and structured approach to software development. Through these enhancements, this application is expected to significantly assist HR departments in efficiently managing employee data, expediting leave request processing, and simplifying the generation of comprehensive reports. The anticipated outcomes of this research are expected to equip HR professionals with the necessary tools to efficiently navigate these intricate tasks, ultimately enhancing organizational efficiency and effectiveness.